2021
DOI: 10.1111/liv.15093
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolic and microstructural alterations associated with hepatitis C virus infection, autoimmune hepatitis and primary biliary cholangitis

Abstract: Background and Aims Neuropsychiatric symptoms in hepatitis C (HCV) patients resemble those of patients with autoimmune hepatitis (AIH) or primary biliary cholangitis (PBC), whilst the mechanisms behind them are unknown. Here we looked for cerebral metabolic and/or microstructural alterations in patients with HCV, AIH or PBC as possible causes behind these symptoms. Methods Patients with HCV infection (n = 17), AIH (n = 14) or PBC (n = 11) and age‐adjusted healthy controls (n = 18) underwent brain magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
1
0
1
Order By: Relevance
“…Here we demonstrate that in people with APRI or FIB4 identi ed brosis relative to those without serum biomarkers of brosis, levels of striatal Cho and tCr and pontine mI are high. These ndings are consistent with the literature demonstrating higher than control levels of Cho, tCr, and mI in various ROIs, including basal ganglia, in individuals with HCV (Forton et al 2001;Forton et al 2002;McAndrews et al 2005;Reichardt et al 2022). The current study, however, extends the literature by suggesting that liver brosis and not HCV per se is responsible for the elevation in striatal Cho, whereas elevations in mI and tCr may be better explained by the presence of HCV (cf., Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…Here we demonstrate that in people with APRI or FIB4 identi ed brosis relative to those without serum biomarkers of brosis, levels of striatal Cho and tCr and pontine mI are high. These ndings are consistent with the literature demonstrating higher than control levels of Cho, tCr, and mI in various ROIs, including basal ganglia, in individuals with HCV (Forton et al 2001;Forton et al 2002;McAndrews et al 2005;Reichardt et al 2022). The current study, however, extends the literature by suggesting that liver brosis and not HCV per se is responsible for the elevation in striatal Cho, whereas elevations in mI and tCr may be better explained by the presence of HCV (cf., Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…Another study utilizing brain MRI testing and MR spectroscopy have found similar perturbations in brain photon density and increase in metabolites including N-acetyl-aspartate, and choline in regional white matter regions in patients with either AIH, HCV or PBC, raising the possibility of shared pathophysiological mechanisms across these conditions. However in this study, there were no correlations between MRI/MR spectroscopy findings with neuropsychological dysfunction (Reichardt et al, 2022).…”
Section: Autoimmune and Cholestatic Liver Diseasecontrasting
confidence: 82%